Novel two-chamber tubular microbial desalination cell for bioelectricity production, wastewater treatment and desalination with a focus on self-generated pH control - Jafary, Tahereh; Al-Mamun, Abdullah; Alhimali, Halima; Baawain, Mahad Said; Rahman, Sadik; Tarpeh, William A.; Dhar, Bipro Ranjan; Kim, Byung Hong (ELSEVIER, 2020)
Microbial desalination cell (MDC) is a new ecofriendly technology that desalinates sea or brackish water by utilizing the electrical energy produced from the oxidation of organics in wastewater. However, pH imbalance as a result of proton accumulation in the anolyte and proton consumption in the catholyte significantly reduces its performance. This research demonstrated, for the first time, the proof-of-concept for a two-chamber tubular MDC (TTMDC) with a new arrangement of the anion and cation exchange membranes. The novel design was aimed to (i) mitigate the pH imbalance through a self-generated pH control mechanism, (ii) reduce internal resistance, and (iii) enhance the recovery of bioenergy in MDC using real seawater as desalination liquid. The results showed that the pH was promisingly balanced using a non-buffered domestic wastewater as the electrolyte with a significant high energy production (8 mW), current generation (43 mA), coulombic efficiency (84%), COD removal (85%) and low internal resistance (10.5 Omega) with 24.3 mg/h of desalination rate in batch operation. The study demonstrated a very promising design of MDC to achieve both the goals of high energy recovery and salt removal with self-generated pH control.